VA Provider Perspectives on Coordinating COPD Care Across Health Systems - Rinne, Seppo T. (J Gen Intern Med, 2019)
BACKGROUND: More and more Veterans are receiving care from community providers, increasing the need for effective coordination across health systems. For Veterans with chronic obstructive pulmonary disease (COPD), this need is intensified by complex comorbidity patterns that often include multiple providers co-managing patient care. OBJECTIVES: We sought to understand how VA providers perceive coordination with community providers for Veterans with COPD. DESIGN: Qualitative study of VA providers. METHODS: We selected six geographically diverse VA sites and conducted semi-structured telephone interviews with providers practicing in inpatient and/or outpatient settings who care for Veterans with COPD. MAIN MEASURES: Interviews focused on communication with community providers about discharge information and clinic management. We analyzed responses according to the principles of conventional content analysis, allowing inductive themes to emerge. KEY RESULTS: We interviewed 25 providers during the period of June to October 2017. Qualitative data analysis yielded five themes: (1) VA providers perceive communication challenges between VA and community providers, including difficult, inadequate, and delayed communication; (2) communication is facilitated by personal relationships across health systems; (3) the lack of electronic health record (EHR) interoperability impairs communication, resulting in transmission of unstructured data; (4) poor communication leads to duplicative efforts and wasted resources; and (5) providers frequently rely on patients to communicate about care taking place in the community. CONCLUSIONS: VA providers described major challenges in coordinating with community providers, leading to perceptions of delayed, missed, or duplicative care and jeopardizing the overall quality, safety, and efficiency of Veteran care. Our study highlights the need for system-level solutions to support coordination across health systems for Veterans with COPD and may have implications for other conditions that lead to recurrent hospitalization and/or care in the community.